Insurance policy thresholds for economic growth in Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study investigates the role of insurance in economic growth on a panel of forty-eight countries in Africa for the period 2004-2014. The research question the study seeks to answer is the following: what thresholds of insurance penetration positively affect economic growth in Africa? The empirical evidence is based on Generalized Method of Moments. Life insurance increases economic growth while the effect of non-life insurance is not significant. Increasing both life insurance and non-life insurance has negative net effects on economic growth. From an extended analytical exercise, 4.149 of life insurance premium (% of GDP) is the minimum critical mass required for life insurance to positively affect economic prosperity while 1.805 of non-life insurance premium (% of GDP) is the minimum threshold required for non-life insurance to positively affect economic prosperity. Thresholds are also provided from the Hansen (1999) Panel Threshold Regression technique using a balanced sample of 28 countries.
Keywords: I28; I30; G20; O16; O55; 330; Insurance; Economic Growth